A novel tool for modeling the near- and far-field dispersion of brine effluent from desalination plants - Porto Pereira, Silvano; Rodrigues, Melissa Fontenelle; Rosman, Paulo Cesar Colonna; Rosman, Patrícia; Bleninger, Tobias; Lima Neto, Iran Eduardo; Teixeira, Carlos E. P.; Sola, Iván; Sánchez Lizaso, José Luis (Frontiers in Marine Science, 2024)
Regardless of the specific technology adopted, the use of desalination to produce fresh water from seawater results in a discharge of brine effluent containing a high concentration of salts and other desalination by-products that must be dealt with appropriately. Until now, this effluent has most commonly been discharged into the sea through a submarine outfall. Computational tools are used to simulate the behavior of these brine discharges to minimize their impact on the marine environment. Environmental assessments of desalination plants that are made using these tools can include consideration of the rates of effluent production and flow, diffuser configurations, marine conditions (e.g., currents, tides, salinity, temperature), and the proximity of plants to environmentally significant areas. Computational tools can also assist in the design of programs for monitoring the surroundings of brine disposal points. In this study, we developed a new tool for modeling brine discharges from submarine outfalls based on an adaptation of a near-field mathematical model coupled with a Lagrangian model. This new model was specifically designed for application to negatively buoyant effluent discharges. The near-field dilution results that were obtained for various current velocities and different diffuser vertical inclinations using this tool were compared with those obtained using a reference tool (Visual Plumes), considering four different desalination plants. Excellent correlation and a mean absolute percentage error lower than 10% were obtained between the two sets of results along with good reproducibility. Additionally, the existence of an integrated wave propagation model in the simulation software allowed the analysis of changes in the brine plume direction produced by waves formed far from the outfall area. Using the new model, it was possible to evaluate how the diffuser configuration affected the performance of the diffuser line, and the saline plume generated by the combined Lagrangian and near-field model realistically reproduced the behavior of a submarine brine outfall. This combined model is potentially applicable to a range of other situations, including studies that aim to minimize the environmental impact of desalination plants based on considerations of outfall locations and optimization of the diffuser configuration.